A Combined Packed‐Bed Friction Factor Equation: Extension to Higher Reynolds Number with Wall Effects. Issue 3 (5th February 2013) - Harrison, Luke D.; Brunner, Kyle M.; Hecker, William C.
Significance A unique combination of classic packed bed friction factor equations and newly refit correlation constants is proposed which produces a new friction factor correlation which significantly improves predictions in high turbulence regimes, high porosity regimes, and high wall effect regimes.